New physicochemical interpretations for the adsorption of food dyes on chitosan films using statistical physics treatment. (15th March 2015) - Dotto, G.L.; Pinto, L.A.A.; Hachicha, M.A.; Knani, S.
Highlights: Dyes adsorption on chitosan films was studied by the statistical physics treatment. The sulfonated groups of the dyes were fundamental for the adsorption process. At higher temperatures, more adsorption sites remained unoccupied. The interactions occurred by electrostatic interactions and hydrogen bonds. Abstract: In this work, statistical physics treatment was employed to study the adsorption of food dyes onto chitosan films, in order to obtain new physicochemical interpretations at molecular level. Experimental equilibrium curves were obtained for the adsorption of four dyes (FD&C red 2, FD&C yellow 5, FD&C blue 2, Acid Red 51) at different temperatures (298, 313 and 328 K). A statistical physics formula was used to interpret these curves, and the parameters such as, number of adsorbed dye molecules per site ( n ), anchorage number ( n ′), receptor sites density ( N M ), adsorbed quantity at saturation ( N asat ), steric hindrance ( τ ), concentration at half saturation ( c 1/2 ) and molar adsorption energy (Δ E a ) were estimated. The relation of the above mentioned parameters with the chemical structure of the dyes and temperature was evaluated and interpreted.